2004
DOI: 10.1016/s0377-1237(04)80058-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation Versus Echocardiography in the Assessment of Rheumatic Heart Disease

Abstract: Background: Rheumatic heart disease (RHD) is still a common form of heart disease among children and young adults, especially in developing countries like India. Between 1940 and 1983, the prevalence rate of RHD varied from 1.8 to 11 per 1000 (national average 6 per 1000), while between 1984 and 1995 the rate varied from 1 to 5.4 per 1000 [1]. The study was carried out to assess the accuracy of a medical student's clinical evaluation of valvular heart disease and compare it with that of an echocardiographic ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…The high specificity indicates the ease of clinical diagnosis when signs are florid. Kolo et al [8] in their study also reported the confirmation by In contrast, the sensitivity of clinical examination for RHD was particular low and corroborated the findings by Kolo et al [8] and Reddy et al [16] Specificity was, however, high. More cases were detected at echocardiography in this study for which the indication for the study was initially different.…”
Section: Discussionsupporting
confidence: 73%
“…The high specificity indicates the ease of clinical diagnosis when signs are florid. Kolo et al [8] in their study also reported the confirmation by In contrast, the sensitivity of clinical examination for RHD was particular low and corroborated the findings by Kolo et al [8] and Reddy et al [16] Specificity was, however, high. More cases were detected at echocardiography in this study for which the indication for the study was initially different.…”
Section: Discussionsupporting
confidence: 73%
“…We conducted this study to assess the accuracy of clinical diagnosis of congenital heart diseases made by the post graduate student by comparing it with echocardiography. Various studies have been done in children and adults where clinical judgment was compared with the echocardiography for diagnosis of various cardiac disorders [12,13,14,15]. We studied80 cases ofcongenital heart diseases from 1 month to 12 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…The simplified echocardiography scoring system to diagnose RHD introduced by Nunes et al offered a more practical and simpler criterion and is suitable for handheld echocardiography application (10). The accuracy of echocardiographic examination even by a handheld echocardiography tool was significantly better than cardiac auscultation alone (1,16,22,23). Most of the RHD screening programs utilized portable echocardiography for more comfortable mobility in remote areas, and in general, they showed a reasonable value for RHD screening.…”
Section: What Can We Do In Indonesia?mentioning
confidence: 99%